Pengaruh Ulasan Produk, Diskon dan Keamanan Transaksi Terhadap Keputusan Pembelian di Lazada: Survei Pada Pengguna Lazada di Wilayah Karanganyar - Resa Agustina Perdana; Retno Susanti (Universitas 45 Surabaya, 2024)
This study uses a survey method conducted on Lazada consumers in Karanganyar to obtain primary data. The population of this study includes all consumers who shop on Lazada, the exact number is unknown. The sampling technique uses a non-probability sampling technique with a purposive sampling method from 100 respondents. The data analysis techniques used were multiple linear regression analysis, t-test, F-test and determination coefficient test. The results of validity tests and reliability tests that all statements regarding product reviews, discounts, transaction security and purchase decisions are declared valid and reliable. The results of the classical assumption test showed that all variables passed the test of multicollinearity, autocorrelation, heteroscedasticity and normality with normal distribution. The results of the linear regression analysis show that the variables of product reviews, discounts and transaction security have a positive influence on Lazada's purchase decisions. The results of the t-test showed that product reviews had a significant effect on Lazada's purchase decisions, discounts had a significant effect on purchase decisions, and transaction security did not have a significant effect on Lazada's purchase decisions. The results of the F test show that the regression model used is correct. The results of the determination coefficient test showed that the contribution of the influence of the independent variable on the bound variable was 47.3%, the remaining 52.7%.